sqrt(x+12) - sqrt(x-9) = 3sqrt(x+12) = 3 + sqrt(x-9)taking square on both side,x+12 = 9 + x -9 +2.3.sqrt(x-9)x+12 = x+6sqrt(x-9)12=6sqrt(x-9)2= sqrt(x-9)

squaring both side,

4= x-9

x= 13

Please appreciate my help, by selecting my answer as the best, and add me as your tutor, Thanks!

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up